Zest Application Timings for Efficacy in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
This study was conducted to compare Zest (nicosulfuron) herbicide at two rates and two application timings for efficacy in grain sorghum. Palmer amaranth control was best when a preemergence (PRE) herbicide was followed by a late postemergence (LPOST) treatment. Zest at 0.67 or 1.33 oz/a provided the best velvetleaf and shattercane control. Either rate of Zest applied early postemergence (EPOST) controlled green foxtail more than 90%, but the higher rate was required for greater than 90% control when applications were delayed until LPOST.
Keywords: herbicide-resistant grain sorghum; herbicide tolerance